The Influence of Collaborating Strategy in Improving Employees’ Performance in Insurance Companies in Homa Bay County, Kenya - Kalei, Anne (East African Scholars Journal of Economics, Business and Management, 2018)
Research in organizational conflict and its management has gained much currency in contemporary times. Accordingly, this study evaluates the influence of collaborating strategy in improving employees’ performance in insurances companies in Homa Bay County Kenya. The study anchored in the Group Conflict Process Theory developed by Robbins. Descriptive research design was adopted. Stratified sampling was used to classify employees then census sampling used to select 4 branch manager, 4 branch administrator, and 29 unit managers. Proportionate and simple random sampling was used to select 140 financial advisors. Reliability of the self- administered questionnaire was tested using Cronbach Alpha. Quantitative data was analyzed using descriptive and inferential statistics. The study concluded that there was a positive relationship between collaborating strategy and employee performance. The study recommends that managers should apply collaborating strategies such as integrating manager’s ideas with those of subordinates to come up with a decision jointly.
Keywords: Conflict; Collaborating; Employee; Performance